Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1159/000342086
|View full text |Cite
|
Sign up to set email alerts
|

Trunk and Lower Limb Fat Mass Evaluated by Dual-Energy X-Ray Absorptiometry in a 20- to 80-Year-Old Healthy Italian Population

Abstract: Background and Aims: Global fat mass distribution seems to correlate with different levels of cardio-metabolic risk; centrally distributed fat carries a high risk of cardiovascular disease, while lower limb adiposity may have a protective effect against insulin resistance. Reference data regarding body composition have already been published for the Italian population; the aim of this study was to add reference values for trunk and lower limb fat mass, and their ratio (TLR), developing percentile distributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
1
2
1
Order By: Relevance
“…Our data are different from the published body composition indices in a 20-to-80-year-old healthy Italian population [18].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our data are different from the published body composition indices in a 20-to-80-year-old healthy Italian population [18].…”
Section: Discussioncontrasting
confidence: 99%
“…However, data of both studies are similar for the total body LM, which is decreasing with advancing age. A similar trend for increasing the total body FM and % FM throughout life was observed in Italian subjects [18,19]. On the contrary, a study in healthy Brazilian women registered a bimodal distribution of body fat-increasing until 50-59, with a slight subsequent decrease [17].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The predictive body fat equation developed from the Western population might not be appropriate for application to the Asian population. It has been demonstrated that body fat values are not consistent between young, middle-aged, and older-aged males (Coin et al, 2012;Ihasz, Finn, Lepes, Halasi, & Szabo, 2015;Larsson et al, 2015). Previous studies have shown that lower body fat was observed by active men compared to sedentary counterparts (Kyle, Morabia, Schutz, & Pichard, 2004;Scheers, Philippaerts, & Lefevre, 2013).…”
Section: Introductionmentioning
confidence: 96%